1997
DOI: 10.1083/jcb.138.4.747
|View full text |Cite
|
Sign up to set email alerts
|

Apical Enrichment of Human EGF Precursor in Madin-Darby Canine Kidney Cells Involves Preferential Basolateral Ectodomain Cleavage Sensitive to a Metalloprotease Inhibitor

Abstract: EGF precursor (proEGF) is a member of the family of membrane-anchored EGF-like growth factors that bind with high affinity to the epidermal growth factor receptor (EGFR). In contrast to human transforming growth factor-α precursor (proTGFα), which is sorted basolaterally in Madin-Darby canine kidney (MDCK) cells (Dempsey, P., and R. Coffey, 1994. J. Biol. Chem. 269:16878–16889), we now demonstrate that human proEGF overexpressed in MDCK cells is found predominantly at the apical membrane domain under steady-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
88
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 59 publications
9
88
3
Order By: Relevance
“…Newly synthesized ligands are inserted into the plasma membrane, whereupon they undergo ectodomain cleavage to release soluble growth factor. We previously studied the biosynthesis and trafficking of EGF, TGF-α (TGFA), and amphiregulin (AREG) in polarized Madin-Darby canine kidney (MDCK) cells (3)(4)(5). These ligands have distinct motifs that govern their basolateral sorting (6)(7)(8).…”
mentioning
confidence: 99%
“…Newly synthesized ligands are inserted into the plasma membrane, whereupon they undergo ectodomain cleavage to release soluble growth factor. We previously studied the biosynthesis and trafficking of EGF, TGF-α (TGFA), and amphiregulin (AREG) in polarized Madin-Darby canine kidney (MDCK) cells (3)(4)(5). These ligands have distinct motifs that govern their basolateral sorting (6)(7)(8).…”
mentioning
confidence: 99%
“…EGF is delivered equally to both the apical and basolateral surface, but is selectively cleaved from the basolateral surface (Dempsey et al, 1997). In this study, we have shown that BTC is preferentially localized to the basolateral surface under steady-state conditions in polarized MDCK cells.…”
Section: Preferential Sorting Of Btc In Polarized Epithelial Cellsmentioning
confidence: 68%
“…These studies have established that spatially controlled ligand trafficking regulates EGFR activity. For example, EGF is delivered to both the apical and basolateral surfaces, but is preferentially cleaved from the basolateral surface (Dempsey et al, 1997). Basolateral EGF delivery is dependent on a PxxP motif (where x denotes any amino acid) within its cytoplasmic domain (Groenestege et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are suggestions of other ligand-shedding activities, including serine proteases (Pandiella et al 1992;Le Gall et al 2004). Tissue-specific heterogeneity in the molecular weight forms of cleaved ligands also suggests that different sheddases exist (Dempsey et al 1997). Furthermore, given that many signaling components are conserved between flies and mammals, a role for rhomboids in mammalian EGFR ligand cleavage is also possible.…”
Section: Active Mammalian Rhomboidsmentioning
confidence: 99%